Antioxidant activity measurement and potential antioxidant peptides exploration from hydrolysates of novel continuous microwave-assisted enzymolysis of the Scomberomorus niphonius protein. (15th May 2017) - Huang, Yipeng; Ruan, Guihua; Qin, Zhijun; Li, Haiyun; Zheng, Yanjie
Highlights: A cMAED method was developed for protein digestion to obtain antioxidant peptides. The cMAED is superior to the CHED for antioxidant peptide acquisition. Eight potential antioxidant peptides were identified and discussed. Abstract: A novel continuous microwave-assisted enzymatic digestion (cMAED) method is proposed for the digestion of protein from Scomberomorus niphonius to obtain potential antioxidant peptides. In this study, bromelain was found to have a high capacity for the digestion of the Scomberomorus niphonius protein. The following cMAED conditions were investigated: protease species, microwave power, temperature, bromelain content, acidity of the substrate solution, and incubation time. At 400 W, 40 °C, 1500 U·g −1 bromelain, 20% substrate concentration, pH 6.0 and 5 min incubation, the degree of hydrolysis and total antioxidant activity of the hydrolysates were 15.86% and 131.49 μg·mL −1, respectively. The peptide analyses showed that eight of the potential antioxidant peptide sequences, which ranged from 502.32 to 1080.55 Da with 4–10 amino acid residues, had features typical of well-known antioxidant proteins. Thus, the new cMAED method can be useful to obtain potential antioxidant peptides from protein sources, such as Scomberomorus niphonius .